Learning Improvement in Number Pattern using Cooperative Learning Model - Herli Br Nainggolan (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2022)
This study aims to increase knowledge and understanding of students whenlearning number pattern. Each individual does not know for sure where to start with the right and not difficult counting pattern. The method with a quantitative descriptive research approach. Classroom Action Research (CAR) is a way of determining how to obtain data on these variables. In research activities, this method of obtaining data is known as the data collection method. The participants of this research were eighth grade of A students, totaling 35 students in SMPN 4 Sungai Raya. Based on the results of the research, it can be concluded that 15 students passed with a percentage of 42% in the Pre-cycle. Moreover, 24 students passed with a percentage of 68% and continued to Cycle II. There were 31 students passed with a percentage of 88% and 4 students (12%) who have not passed. In sum, Cooperative Learning Model can help students to understand number pattern topic.